Otoritas Notaris/PPAT Dalam Menerima Titipan Pembayaran Pajak Bea Perolehan Hak Atas Tanah Dan Bangunan - Hardhiyanto, Iqbaal Bagus; Sukmariningsih, Retno Mawarini (PSHPM Untag Semarang, 2025)
The challenges faced by Notaries and Land Deed Officials (PPAT) in managing the Land and Building Rights Acquisition Tax (BPHTB) are significant within Indonesia's land administration and taxation system. A major challenge is determining the accurate BPHTB amount due to discrepancies between the recorded Sale Value of Tax Objects (NJOP) and the actual market value of the property. Since NJOP often does not reflect the true market value, it complicates the calculation of BPHTB, impacting accuracy and compliance with tax regulations. Frequent changes in tax policies, such as BPHTB rate adjustments and new administrative procedures, further complicate the tasks of Notaries and PPAT. To address these issues, they must take several strategic steps: regularly updating their knowledge through training and seminars (as per Law No. 30 of 2004 on Notarial Positions), utilizing digital resources like official tax authority websites, and maintaining effective communication with local tax authorities. Additionally, adopting integrated information systems that can be updated with the latest policies is crucial. Joining professional associations like the Indonesian Notaries Association (INI) or the Association of Land Deed Officials (IPPAT) provides valuable updates and training, as outlined in Government Regulation No. 37 of 1998 on the Regulation of Land Deed Officials. Regular internal training and collaboration with tax consultants who have access to the latest information will enhance their ability to adapt to policy changes. By implementing these measures, Notaries and PPAT can better manage policy changes, ensure regulatory compliance, and deliver accurate and reliable services. Their role is essential in supporting transparent tax administration and maintaining the integrity of the land and tax system in Indonesia, thus contributing to sustainable economic development and legal certainty.